The utilization of medicinal plants local wisdom of the Salako Dayak Tribal Community in Kaliau Village, Sambas District - Panjaitan, Ruqiah Ganda Putri; Titin, Titin; Afandi, Afandi; Ningsih, Kurnia; Wahyuni, Eko Sri; Fajri, Hayatul; Yuniarti, Anisyah; Tenriawaru, Andi Besse; Yeni, Laili Fitri; Aprilianti, Melda (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Kaliau Village has potential that can be further explored, both socially and culturally. One of the local wisdom owned by the Dayak Salako Tribal Community in Kaliau Village is the utilization of plants as the resources of traditional medicines. This research aims to gain information about the local wisdom of the Dayak Salako Tribal Community in Kaliau Village, Sambas Regency in using medicinal plants. This research was conducted in Kaliau Village, Sajingan Besar District, Sambas Regency, West Kalimantan Province. We used all of tthe Dayak tribal community in Kaliau Village as population. The sample of informants was taken using the snowball sampling method. The qualitative method is used in this research by collecting the data, interviews, observation, and documentation of potential medicinal plants in Kaliau Village. Dayak Salako Tribal Community in Kaliau Village has utilized fifteen species of single plants and two concoctions as alternative medicines to treat certain diseases. Several plants can only utilize the leaves part, bark, pulp of fruit, and roots. However, several plants can also utilize all of the parts. Processing plants for traditional medicines is drinking, eating, or applying them to body parts.